Pengaruh Pemberian Jenis Pakan yang Berbeda terhadap Laju Pertumbuhan Benih Ikan Lele (Clarisa sp) - Mira Wahyuni; Kana Furkonah Pasaribu; Mega Wahyuni Nasution; Raja Siti Aisyah (Departement of Mathematics Education, 2023)
The general public cultivates catfish a lot because catfish has a fairly high economic value and is of interest to many groups. Feeding is very influential on the high or low production of fish given. The purpose of conducting this research was to find out about giving different types of feed on the growth rate of catfish seeds and reducing feed costs to meet the needs of catfish consumption and increase the profits obtained. This type of research is an experiment using a completely randomized design (CRD) with different feeding. This research was conducted in November-December. The materials used are catfish seeds, pellets and kale. The tools needed in this study were closed basins, hoses, containers and scales. Where the data taken in this study is catfish growth data which includes the length and weight of the seeds. It can be concluded that the growth of catfish can be seen from the difference in the effect of natural feed, where the weight and length of the artificial feed are greater than the natural feed, namely 9.8 cm and 3 grams.